1.5-μm and 10-Gb s−1 etched mesa buried heterostructure DFB-LD for datacenter networks. (18th August 2015) - Kwon, Oh Kee; Lee, Chul Wook; Leem, Young Ahn; Kim, Ki Soo; Oh, Su Hwan; Nam, Eun Soo
Abstract: We report a 1.5 μ m and 10 Gb s −1 etched mesa buried heterostructure λ /4-shifted distributed feedback laser diode (DFB-LD) for the low-cost application of WDM–based datacenter networks. To reduce the threshold current and improve the modulation bandwidth in a conventional p-/n-/p-InP current blocking structure, a thin undoped-InP (u-InP) layer was inserted between the side walls of the active region and the p-InP layer (i.e., a u-/p-/n-/p-InP structure), and the region containing the active region and the current blocking structures was etched in a mesa form (i.e., an etched mesa). From this work, it was found that a 300 μ m long anti-reflection (AR)-AR DFB-LD with a mesa width of 8 μ m is reduced by about 25% while a side mode suppression ratio is >50 dB and a 3 dB bandwidth is >10 GHz at a current of 40 mA; in addition, it shows a clear eye-opening with a dynamic extinction ratio of >4.5 dB at 10 Gb s −1, and a power penalty of <1 dB after a 2 km transmission.